Assessment of the Implemented Kapatid Mentor ME Program (KMME) of the Department of Trade and Industry (DTI) in Region VII, Philippines - Almaden, Antoniette; Yu, Bryll (JPAIR Multidisciplinary Research, 2022)
The Kapatid Mentor ME (KMME) Program is a 10-module mentorship and coaching program initiative of the Department of Trade and Industry (DTI) and Philippine Center for Entrepreneurship (PCE) - Go Negosyo to help the country’s Micro and Small Enterprises (MSEs). Since the COVID-19 pandemic started, the program was transitioned from face-to-face to an online learning platform. The study aimed to assess the implementation of the program from the period 2016 to 2021 to streamline the future direction and craft a more holistic initiative for MSEs. The study used a descriptive research design. An online questionnaire was administered to the 257 respondents clustered by Region VII provinces. There were advantages and disadvantages identified for both learning approaches used. The respondents considered the advantages of face-to-face learning as hands-on learning, easy networking, and a conducive learning environment. Also, the advantages of the online learning approach were accessibility of time and place, comfort, and abundant online resources. It was discovered that 74.75% of the mentee graduates had improved their business status after joining the program. To ensure sustainability and scaling up of MSEs, strengthening the monitoring phase and maximizing the enterprise development track tool are recommended to address the gap of the 25.25% non-improving mentee graduates through concrete and specific intervention schemes recommended.